Propuesta para el desarrollo de los manuales de operación para el centro de transformación y adecuación (CETA) del centro de procesos e innovación para la industria sostenible (CEPIIS) (2023)
This project was developed in order to carry out the operation manuals of the equipment belonging to the Transformation and Adaptation Center (CETA) of the Center for Processes and Innovation for Sustainable Industry (CEPIIS) of the University of America taking into account equipment safety parameters, operating and installation conditions, risk analysis tools such as What If, HAZOP and Bow-Tie, as well as the different. Initially, an extensive bibliographic review was carried out in which the basic concepts for the understanding and good development of this project were determined. Concepts such as operation manual, pilot plant, scaling, reactor bench, evaporator train and other terminology necessary for the preparation of the operation manuals were taken into account. Then, a context was made in which a brief description of all the areas of the CEPIIS and the equipment that is handled in each of them was presented, delving a little deeper into the area of the CETA and the equipment that is handled there, which is the reactor bank and the evaporator train.